Tellurite Promotes Stress Granules and Nuclear SG-Like Assembly in Response to Oxidative Stress and DNA Damage - Gaete-Argel, Aracelly; Velásquez, Felipe; Márquez, Chantal L.; Rojas-Araya, Barbara; Bueno-Nieto, Constanza; Marín-Rojas, Josefina; Cuevas-Zúñiga, Miguel; Soto-Rifo, Ricardo; Valiente-Echeverría, Fernando (Frontiers in Cell and Developmental Biology, 2021)
Tellurium oxyanion, tellurite (〖TeO〗_3^(-2)), is a highly toxic compound for many organisms. Its presence in the environment has increased over the past years due to industrial manufacturing processes and has been associated with adverse effects on human health. Although tellurite induces the phosphorylation of eIF2α, DNA damage and oxidative stress, the molecular mechanisms related to the cellular responses to tellurite-induced stress are poorly understood. In this work, we evaluated the ability of tellurite to induce phosphorylation of eIF2α, stress granules (SGs) assembly and their relationship with DNA damage in U2OS cells. We demonstrate that tellurite promotes the assembly of bona fide cytoplasmic SGs. Unexpectedly, tellurite also induces the assembly of nuclear SGs. Interestingly, we observed that the presence of tellurite-induced nuclear SGs correlates with γH2AX foci. However, although H2O2 also induce DNA damage, no nuclear SGs were observed. Our data show that tellurite promotes the assembly of cytoplasmic and nuclear SGs in response to oxidative stress and DNA damage, revealing a new aspect of cellular stress response mediated by the assembly of nuclear stress granules.